Coastal Landscape Characterization. The Case of the Sartol Seacoast, Bushehr, Iran - Sheibani, Mahdi; Razavi, Niloofar; Mofrad, Fahimeh (Ri-Vista. Research for landscape architecture, 2017)
The pressures of the industrial development and the interactions of humans and environment constantly strain coastal landscapes. As a resolution, documenting the authentic conditions of landscapes, as well as their changing character, is suggested as a monitoring and safeguarding strategy for sustainability of all landscapes, including coastal landscapes. In that regard, this paper describes a method for classifying coastal landscape characters in Sartol costal area in Bushehr, Iran, with special emphasis on the geomorphological features. The emphasis of geomorphological features of the landscape is meant to raise the awareness in the local community on the one hand, and is a measure to control the possible negative changes imposed by the developments of the site. Starting from a review of relevant theories of landscape classification, this approach examines the important and necessary steps in the documentation of landscape character, and continues to test the method in organizing the inventory and basic characterization of Sartol.